Effects of Organic and Inorganic Sources of Nutrient on Yield, Quality and Shelf Life of Broccoli - Tarafder, Sushanta Kumar; Biswas, Mrityunjoy; Alim, Md. Abdul; Mondal, Asit Baran; Alam, Mahfujul (Current Research in Agricultural Sciences, 2022)
The study was conducted at Jashore Sadar Upazila, Bangladesh during 2019-20 and 2020-21 to evaluate the effects of organic and inorganic nutrient sources on yield, quality and shelf life of broccoli through Randomized Complete Block Design with three replications and ten treatments which were: T1 = Soil test based 100% NPK, T2 = Vermicompost 4 t ha-1 + soil test based 50% NPK, T3 = Vermicompost 2 t ha-1 + 100% NPK, T4 =Tricho-compost 2 t ha-1 + 100% NPK, T5=FYM 6 t ha-1 + 100% NPK, T6 = Tricho-compost 4 t ha-1 + 50% NPK, T7 =FYM 12 t ha-1 + 50% NPK, T8= Vermicompost 1 t ha-1 + 125% NPK, T9= Tricho-compost 1 t ha-1 + 125% NPK, T10= FYM 3 t ha-1+125% NPK. Completely Randomized Design was designed to determine the shelf life of broccoli with three replications considering three factors; (i) Organic and inorganic nutrient sources; (ii) storage materials at room temperature (iii) storage materials at cold storage. Findings revealed that treatment T3 produced significantly maximum marketable curd yield 30.57 and 30.23 t ha-1 and the highest Benefit Cost Ratio (3.70 and 3.66) in the respective years. The treatment T2 effectively increased post-harvest quality attributes and also recorded the highest shelf life 8.36 and 8.55 days at room temperature (14-240 C with RH 60-65%), 26.33 and 27.25 days at cold storage (4° C with RH 90-95%) condition using High -Density Polyethylene (HDP; 15 micron) vacuum pack during the years of 2019-20 and 2020-21 respectively.